Analisis Efektivitas Pengelolaan Kawasan Konservasi Perairan Gili Trawangan Pada Zona Perikanan Berkelanjutan Di Masa Pandemi Covid 19 - Junaidi; Handri Jurya Parmi (LPPM Universitas Gunung Rinjani, 2023)
The flexibility and supportive situation provide an overview of whether or not the management of a conservation area is effective. Thus the research was conducted on how the effectiveness of the management of the Gili Trawangan waters conservation area during the covid 19 pandemic. The purpose of this study was to compare the effectiveness of the management of the Gili Trawangan waters conservation area during the covid 19 pandemic with the effectiveness of management before the covid 19 pandemic, especially in the sustainable fisheries zone. The method used in this study is a qualitative descriptive method, namely analyzing 4 criteria and 4 indicators from 24 indicators of the implementation of technical guidelines for evaluating the effectiveness of conservation area management. matra, as well as several Gili Matra tourism business actors and Gili Trawangan community leaders. The effectiveness of the management of the Gili Trawangan marine conservation area during the COVID-19 pandemic in terms of four criteria and four indicators was found to be ineffective due to budget cuts from the head office. So that there are programs that are routinely every year before Covid cannot be carried out, such as: ecosystem rehabilitation, surveys of important biota habitats and conservation go to schoole, habitat surveys. these programs maximally cause area management to be ineffective. Likewise, the process criteria with indicators for community empowerment and conservation implementation partners are hampered, this is also related to the lack of budget to carry out process indicators. This relatively high level of community knowledge and compliance with conservation is influenced by the holding of local archival principles and guidelines by the conservation village regulation. This conservation regulation is an element of awiq awiq. Likewise with the outcome criteria with indicators of community participation in conservation during the COVID-19 pandemic based on interviews with the head of the pokdarwis tramena and the head of the existing pokmaswas, due to the lack of busyness in the tourism business, most of the people practice doing activities as fishermen and want to care about zone boundaries and utilization. existing zone well. Keywords: effectiveness, conservation, covid 19 Abstrak Tujuan penelitian ini adalah untuk membandingkan efektivitas pengelolaan kawasan konservasi perairan gili trawangan dimasa pandemi covid 19 dengan efektivitas pengelolaan sebelum masa pandemi covid 19 hususnya pada zona perikanan berkelanjutan. Metode yang digunakan dalam penelitian ini adalah metode diskriptif kualitatif yaitu menganalisa 4 kreteria dan 4 indikator dari 24 indikator pelaksanaan pedoman teknis evaluasi efektivitas pengelolaan kawasan konservasi Data direduksi dengan Teknik wawancara mendalam dengan responden yaitu, kepala BKKPN Kupang, ketua POKDARWIS Gili Matra, ketua POKMASWAS gili matra, serta beberapa pelaku usaha pariwisata gili matra dan tokoh masyarakat Gili Trawangan. Efektivitas pengelolaan kawasan konservasi perairan Gili Trawawangan dimasa pandemi covid 19 ditinjau dari empat kreteria dan empat indikator didapatkan tidak epektif ini disebabkan oleh pemotongan anggaran dari kantor pusat. Sehingaga ada program program yang sipatnya rutin tiap tahun sebalum covid tidak bisa dilangsungkan, seperti: rehabilitasi ekosistem, surve habitat biota biota penting dan conservasi go to schoole, survey habitat, Yang masih berjalan tapi volume dikurangi adalah monitoring kesesuaian zonasi dan peruntukananya, Dengan tidak terlaksananya program program ini dengan maksimal menyebabkan pengelolaan kawasan menjadi tidak epektif. Demikian juga dengan kreteria proses dengan indikator pemberdayaan masyarakat dan mitra pelaksanaan konservasi menjadi terhambat ini terkait juga dengan kurangnya anggaran untuk menjalankan indikator proses. Tingkat pengetahuuan dan kepatuhan masyarakat terhadap konservasi relative tinggi ini dipengaruhi oleh pegangan prinsip kearipan kearipan lokal dan panduan oleh perdes konservasi. Perdes konservasi ini merupakan elementasi dari awiq awiq. Begitu juga dengan Kreteria outcome dengan indikator partisipasi masyarakat terhadap konservasi pada masa pandemi covid 19 berdasarkan wawancara dengan ketua pokdarwis tramena dan ketua pokmaswas yang ada, karena kurangnya kesibukan usaha pariwisata maka sebagian besar masyarakat berlaih melakukan aktivitas sebagai nelayan dan mau peduli terhadap batasan zona dan pemanfaatan zona yang ada dengan baik. Kata kunci: efektivitas, konservasi, covid 19